The Regulatory Road to Reform: Bureaucratic Activism, Agency Advocacy, and Medicaid Expansion within the Delegated Welfare State. (December 2018) - Pacewicz, Josh
American policymakers delegate the administration of many welfare programs to states, where officials implement them in increasingly diverse ways. Welfare state scholarship has little to say about this subnational policy divergence, and it portrays the complexity of delegated governance as a barrier to nonelite legislative influence. Drawing on an ethnographic study of one state's Medicaid program, this article shows that delegated governance offers ample opportunity for nonelite influence and policy divergence, but through regulatory governance rather than legislative advocacy. Medicaid is opaque to politicians, whose inability to monitor program details creates conditions of bureaucratic autonomy and even activism: health-care agency personnel sequence regulatory tweaks to protect and expand entitlements. But budget cuts, outsourcing, and fraught provider relations also deprive bureaucrats of street-level know-how, and bureaucrats depend on beneficiaries' advocates who selectively illuminate a path to reform. A full rendering of subnational divergence in American federalism requires attention to underexamined factors such as bureaucratic activism, agency advocacy, and regulatory governance.